2016
DOI: 10.1002/pat.3741
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and performance of styrene butadiene rubber filled with modified graphite nanoplatelet and carbon black

Abstract: In our work, effects of 2-mercapto-1-methylimidazole modified graphite nanoplatelet (MMI-GN) and carbon black (CB) on static and dynamic mechanical properties of styrene butadiene rubber (SBR) composites were studied. MMI-GN is synthesized by ball-mill process, and the result reveals that π-π interactions existed between MMI and GN. The results demonstrate that the static and dynamic mechanical performances of SBR/CB/MMI-GN composites are significantly improved over these of SBR/CB and SBR/CB/GN composites. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…The trans >C=CH- (961 cm −1 ) and the vinyl (>C=CH 2 , 905 cm −1 ) are assigned to the SBR backbone38. The characteristic absorption of -C-S- stretching deformation at 1085, 692 cm −1 and 476, 428 cm −1 (related to -S-S- stretching deformation)39 is explained by sulfur cross-linking as shown in Fig.…”
Section: Resultsmentioning
confidence: 88%
“…The trans >C=CH- (961 cm −1 ) and the vinyl (>C=CH 2 , 905 cm −1 ) are assigned to the SBR backbone38. The characteristic absorption of -C-S- stretching deformation at 1085, 692 cm −1 and 476, 428 cm −1 (related to -S-S- stretching deformation)39 is explained by sulfur cross-linking as shown in Fig.…”
Section: Resultsmentioning
confidence: 88%
“…27,28 T g , an important glass transition parameter reflecting the segmental motion of rubber chains, would increase or decrease with the addition of fillers. 17,29,30 What is more, some related studies reported that T g remains unchanged or shows no obvious tendency with the increase of filler content in some cases, 27,31 whose variation is affected by the molecular weight and polarity of rubber, the characteristics of fillers, and so on. 27,29 The results of T g in this work showed no distinct tendency with the increase of CG, which was consistent with the results reported in Reference 27, 31.…”
Section: Immobilized Rubber Layer Of Nbr Compositesmentioning
confidence: 95%
“…Several peaks at 31.6 , 34.3 , and 36.2 , respectively represented the (100), (002), and (101) diffraction peaks of zinc oxide. 17 Figure 5 (a-d) shows the surface morphology of freeze-fractured NBR composites with different CG loadings. Obviously, CG showed good dispersion in the NBR matrix.…”
Section: Dispersion Of Cg In the Nbr Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the designing of new polymeric material and modification of existing polymers for superior properties got great research emphasis. This is because the remarkable advances in polymer industry have a large impact on our daily life, especially clothing, transportation, energy, and medicine . A lot of research has been made over the last several years on chemical functionalization of conventional elastomers by using different reactive groups for producing potentially important materials with different mechanical thermal, electrical, and viscoelastic properties in addition to their specific attributes .…”
Section: Introductionmentioning
confidence: 99%